Performance Comparison of Variational Mode Decomposition and Butterworth in Processing EEG Signals of Autism Patients - Surya Wardana; Melinda Melinda; Rizka Ramdhana; Yunidar Yunidar; Yuwaldi Away; Nurlida Basir (Poltekkes Kemenkes Surabaya, 2026)
Tier 4- Non-Indexed Publication